Persepsi Siswa Mengenai Mitigasi Bencana Gempa di SMA Negeri 1 Suwawa Timur - Lasulika, Cindy Tsasil; Melo, Ramla Hartini (-, 2025)
This study aims to analyze students’ perceptions of earthquake disaster mitigation at SMA Negeri 1 Suwawa Timur, focusing on aspects such as understanding, attitude, preparedness, participation, and evaluation of the school’s mitigation program. A descriptive quantitative method was employed, with data collected through questionnaires completed by students. The results indicate that students' understanding of earthquake mitigation falls into the "very good" category, with an average score of 4.12. Students’ attitudes toward the importance of disaster mitigation and their participation in mitigation activities scored 3.60 and 3.61, respectively, while their evaluation of the school’s mitigation program scored 3.64—all classified as "good." However, students’ preparedness for disaster remains in the "moderate" category, with a score of 3.00. These findings suggest that while the mitigation program is generally effective, further improvement is necessary—particularly in enhancing students’ preparedness—through the development of more interactive and collaborative mitigation initiatives.